Repositório digital como ambiente de inclusão digital e social para usuários idosos - Vechiato, Fernando Luiz [UNESP] (2010)
The contemporary society characterized as information society or net society is closely related to the use of information and communication technologies (ICT), especially the World Wide Web, which makes possible the creation of contents and the information access with no boundaries of time and space. We can see the increase of people using this technology, since its creation in the beginning of 1990 decade, and we can highlight the elderly users. These users find in the Web an environment in which they can develop different activities, as easily dealing with daily duties and getting information about subjects related to aging, among others. However, we verify that the Web information environments do not have an Information Architecture developed with the specific necessities of this public, making difficult the use and access, and then, making hard the digital and social inclusion of this users group. In this context, our objective is to identify elements that enable the social and digital inclusion of the elderly using the study of Information Architecture, Usability, Accessibility and Information Behavior, in the Information Science context, as well as the application of this elements in a digital repository built for the Universidade Aberta à Terceira Idade – UNATI – UNESP. We consider that a digital repository that deals with subjects of interests and production of elderly and that presents inclusive elements makes possible their digital and social inclusion. We used the action-research to realize the research. The action-research makes possible for the researcher and participants the identification of problems and objectives of the research as well as the planning and execution of actions for its resolution. Also for the execution of these actions, focus groups are mainly used to discuss how to guide them... (Complete abstract click electronic access below)